2015
DOI: 10.1074/jbc.m114.633677
|View full text |Cite
|
Sign up to set email alerts
|

YscU/FlhB of Yersinia pseudotuberculosis Harbors a C-terminal Type III Secretion Signal

Abstract: Background: After auto-proteolysis and dissociation, YscU CC is secreted by the T3SS of Yersinia pseudotuberculosis. Results: YscU CC harbors a specific C-terminal T3S signal and its deletion triggers an increase of YscF secretion without affecting Yops secretion. Conclusion: C-terminal end of YscU participate in YscF secretion regulation but not in the substrate specificity switch. Significance: This is the first report of a C-terminal T3S signal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Destabilized YscU mutants that displayed increased rate constants of dissociation also enable secretion of Yops at 30°C, a temperature at which the wild-type strain effectively displays no Yop secretion. In addition, we previously identified a C-terminal secretion signal in YscU CC (29). Taken together, these findings suggest that YscU CC dissociation and subsequent secretion enabled by autoproteolysis play an important role in regulating Yop secretion.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…Destabilized YscU mutants that displayed increased rate constants of dissociation also enable secretion of Yops at 30°C, a temperature at which the wild-type strain effectively displays no Yop secretion. In addition, we previously identified a C-terminal secretion signal in YscU CC (29). Taken together, these findings suggest that YscU CC dissociation and subsequent secretion enabled by autoproteolysis play an important role in regulating Yop secretion.…”
Section: Discussionmentioning
confidence: 66%
“…YscP Protects the Slow Processing Mutant P264A from Autocleavage-It has been shown previously that the dissociation of YscU C into the two polypeptides YscU CC and YscU CN is required for Yop secretion and that YscU CC is subsequently secreted into the culture supernatant (27,29). The secretion of YscU CC through the T3SS is facilitated by a C-terminal secretion sequence, and the non-secreting phenotype observed for yscP-null mutants is partially rescued by the secondary suppressor mutants YscU…”
Section: E332amentioning
confidence: 99%
See 2 more Smart Citations
“…This study, for the first time, showed that FlhB is involved in regulating the flagellar synthesis of important flagellar proteins, and that it affects the secretion of other bacterial proteins in L. monocytogenes . The main function of FlhB in Yersinia pseudotuberculosis is to mediate the transport of T3SS effector molecules and mediate the transport of bacterial toxins into host cells ( Minamino and Macnab, 2000a ; Macnab, 2004 ; Barker and Samatey, 2012 ; Login and Wolf-Watz, 2015 ; McMurry et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%